The Effect of Jigsaw Technique in Reading Comprehension on Recount Text - Herman; Juwita Kristina Sibarani; Hilman Pardede (Cetta: Jurnal Ilmu Pendidikan, 2020)
The objective of this research is to find out the effect of Jigsaw technique on reading comprehension at grade ten of SMA 4 Negeri Pematangsiantar. The research used descriptive quantitative research design by applying Quasi-Experimental design. In conducting this design, the subjects of the research were divided into two groups: experimental group and control group. The treatment is introduced only to the experimental subject. The experimental group is treated by using Jigsaw technique while the control group is treated without Jigsaw technique. The subject of this research was the grade ten students (X PMIA 4 and X PMIA 5) in SMA Negeri 4 Pematangsiantar. The researcher used mobile phone as instrument which recorded video teacher and students activity during teaching and learning process in the class. The result of the research showed that in significance degree of 5%, the value of t-observe > t-table that was (5.55 > 1.669). It could be said that t-observe was higher than t-table. So, the null hypothesis is rejected while the alternative hypothesis is accepted. In other words it can be concluded that the application of Jigsaw teaching technique significantly affects the students’ ability in reading comprehension of recount text at grade ten of SMA Negeri 4 Pematangsiantar.